2015
DOI: 10.1245/s10434-014-4274-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stereotactic Body Radiation Therapy for Pancreatic Cancer: A Single-Institution Experience

Abstract: Background Stereotactic body radiation therapy (SBRT) is a promising option for patients with pancreatic cancer (PCA); however, limited data support its efficacy. This study reviews our institutional experience of SBRT in the treatment of locally advanced (LAPC) and borderline resectable (BRPC) PCA. Methods Charts of all PCA patients receiving SBRT at our institution from 2010 to 2014 were reviewed. Most patients received pre-SBRT chemotherapy. Primary endpoints included overall survival (OS) and local progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
124
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 21 publications
(34 reference statements)
12
124
0
Order By: Relevance
“…Integrating these advances, a recent prospective, multi-institutional trial for patients with LAPC utilizing a 5-fraction regimen of 33 Gy reported rates of grade ≥2 gastritis, fistula, enteritis, and ulcer to be 2% (67). Furthermore, rates of resection among BRPC and LAPC patients are increasing, with 21.6% of patients (79% of whom were LAPC) in a series from Johns Hopkins undergoing resection and 51% of BRPC/24% of LAPC treated at Moffitt with induction FOLFIRINOX (leucovorin, fluorouracil, irinotecan, oxaliplatin) undergoing surgery (26,68). Integration of more active systemic therapies such as mFOLFIRINOX (neoadjuvant modified FOLFIRINOX) with SBRT is now being tested, with early data from a phase I trial using a strategy of 30-36 Gy in 3 fractions to the whole target and a focal 9 Gy integrated boost to the tumor/vessel interface showing no acute grade 3 or 4 complications and a median survival not yet reached (69).…”
Section: Discussionmentioning
confidence: 99%
“…Integrating these advances, a recent prospective, multi-institutional trial for patients with LAPC utilizing a 5-fraction regimen of 33 Gy reported rates of grade ≥2 gastritis, fistula, enteritis, and ulcer to be 2% (67). Furthermore, rates of resection among BRPC and LAPC patients are increasing, with 21.6% of patients (79% of whom were LAPC) in a series from Johns Hopkins undergoing resection and 51% of BRPC/24% of LAPC treated at Moffitt with induction FOLFIRINOX (leucovorin, fluorouracil, irinotecan, oxaliplatin) undergoing surgery (26,68). Integration of more active systemic therapies such as mFOLFIRINOX (neoadjuvant modified FOLFIRINOX) with SBRT is now being tested, with early data from a phase I trial using a strategy of 30-36 Gy in 3 fractions to the whole target and a focal 9 Gy integrated boost to the tumor/vessel interface showing no acute grade 3 or 4 complications and a median survival not yet reached (69).…”
Section: Discussionmentioning
confidence: 99%
“…This dose is similar to those being proposed for high dose stereotactic radiotherapy protocols in the clinic. 27 To assess the cell cycle effects over time we used a flow cytometry protocol that involves combined staining for DNA content, Cyclin A2, and H3S10 phosphorylation, as described by Jacobberger et al 28 This allows cells with a 4N DNA content to be separated into G2 phase (Cyclin A2 positive, pH3S10 negative), early mitosis (Cyclin A2 and pH3S10 positive), metaphase C anaphase (Cyclin A2 negative, pH3S10 positive), and mitotic exit (double negative). As seen in Figures 6A and 6B, there was a decrease in both Cyclin A2 and pH3S10 positive cells 6 h after treatment, followed by recovery of Cyclin A2, particularly in early Sphase, after 16 h, and buildup of Cyclin A2 positive cells at the 4N position after 24 h. At 24 h cells also appeared showing H3S10 phosphorylation, suggesting that the effect of radiation in vivo is to slow transit through G2, rather than G2 arrest.…”
Section: Effects Of Mk-1775 In Combination With Ionizing Radiationmentioning
confidence: 99%
“…Despite the above mentioned characteristics which seem to improve some of the major limits of EBRT, the role of SBRT in LAPC and BRPC is not clearly defined yet, though some interesting preliminary evidence of its activity has been recently reported. As an example, in a single centre institution experience, the authors reported a median OS of 18.4 mo and median PFS of 9.8 mo in 88 patients affected by LAPC and BRPC treated with SBRT (2-30 Gy in five fractions on the planning target volume) with an acceptable toxicity profile (3.4% of > G3 gastrointestinal toxicity) [86] . Furthermore, SBRT led to improved pain control in five out of six studies in which this outcome has been evaluated [87] .…”
Section: Stereotactic Body Radiotherapymentioning
confidence: 99%